The role of conspecifics during pelagic foraging of Magellanic and benthic foraging of Gentoo penguins in the Beagle Channel, Argentina - Harris, Sabrina; Pütz, Klemens; Mattern, Thomas; Scioscia, Gabriela; Raya Rey, Andrea Nélida (Marine Biology)
Seabirds coexist within colonies yet the role of conspecifics, whilst foraging is still poorly understood. In the 2019/20 and 2020/21 breeding seasons Magellanic penguins Spheniscus magellanicus and Gentoo penguins Pygoscelis papua were equipped with video loggers and GPS devices (n = 3 and n = 2, respectively) or only GPS devices (n = 11 and n = 2) at Martillo Island (54°54′ S, 67°23′ W), Argentina and compared with GPS tracks from previous seasons (2014, 2015 and 2017). Magellanic penguins transited in groups with conspecifics to the feeding grounds (up to 13 individuals were recorded simultaneously) in search of pelagic Fuegian sprat Sprattus fuegensis, but then were not filmed in close company of conspecifics during prey capture. Gentoo penguins generally fed on Nototheniid sp. at the seafloor. Contrary to predictions, Gentoo penguins foraged with conspecifics in small groups of 2–4 individuals, they coordinated to dive down, search and ambush prey. Gentoo penguins were also recorded foraging pelagically on Fuegian sprat. Conspecifics play an important role either during the initial search for prey patches, particularly when searching for elusive pelagic prey or during the small-scale search and hunt for benthic prey hidden in the seafloor substrate. The presence of conspecifics seems to be important during foraging for Magellanic and Gentoo penguins and this may be reflecting a positive aspect of coloniality. Fil: Harris, Sabrina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Wildlife Conservation Society; Estados Unidos Fil: Pütz, Klemens. Antarctic Research Trust; Alemania Fil: Mattern, Thomas. University of Otago; Nueva Zelanda Fil: Scioscia, Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Raya Rey, Andrea Nélida. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Wildlife ...